2017
DOI: 10.1016/j.bbadis.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Rutin attenuates doxorubicin-induced cardiotoxicity via regulating autophagy and apoptosis

Abstract: Doxorubicin as anticancer agent can cause dose-dependent cardiotoxicity and heart failure in the long term. Rutin as a polyphenolic flavonoid has been illustrated to protect hearts from diverse cardiovascular diseases. Its function is known to be related to its antioxidant and antiinflammatory activity which may regulate multiple cellular signal pathways. However, the role of rutin on doxorubicin-induced cardiotoxicity has yet to be discovered. In this study, we explored the protective role of rutin on doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…The exact pathogenesis of DOXO-induced cardiotoxicity is not fully understood even if it is assumed that it is multifactorial [ 9 , 10 , 11 , 12 ]. Several lines of evidence indicate that DOXO-induced cardiomyopathy is characterized by abnormal calcium homeostasis, but most of the studies published report only the effects of long-term DOXO-administration [ 13 , 14 , 15 , 16 ]. Recently, we have demonstrated that DOXO administration is able to induce calcium dysregulation and Connexin43 (Cx43) re-arrangement in a rat cardiomyoblast cell line already evident after a short-term administration [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathogenesis of DOXO-induced cardiotoxicity is not fully understood even if it is assumed that it is multifactorial [ 9 , 10 , 11 , 12 ]. Several lines of evidence indicate that DOXO-induced cardiomyopathy is characterized by abnormal calcium homeostasis, but most of the studies published report only the effects of long-term DOXO-administration [ 13 , 14 , 15 , 16 ]. Recently, we have demonstrated that DOXO administration is able to induce calcium dysregulation and Connexin43 (Cx43) re-arrangement in a rat cardiomyoblast cell line already evident after a short-term administration [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have focused concentration on identifying small molecules acting as chaperones to stimulate or stabilize proteins that regulate autophagy [6]. There is evidence indicated that LPS can induce autophagy in macrophages and mice [7,8]. It was reported that cardiac-specific Atg5-defcient mice showed age-related cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, autophagy contributes to mitochondrial function maintenance, resulting in the alleviation of ROS accumulation and apoptosis upon DOX challenge 42,43 . However, autophagy may be promoted by low doses of DOX in cardiomyocytes; this is detrimental to cardiomyocyte survival 44‐46 . It has been reported that preventing autophagy, such as the silencing of beclin‐1 and activation of GATA4 and AKT have been shown to be protective against cardiac cells exposed to DOX 44,45,47 .…”
Section: Discussionmentioning
confidence: 99%